The Writer Alan D. Mickle: Serendipity, Vanity and Obscurity in an Australian Literary Career (Journal of the Association for the Study of Australian Literature, 2009)
This article examines the work of a largely forgotten literary intellectual, Alan D. Mickle (1883-1969). His career testifies to the possibility of living a long, active, varied and productive writing life entirely without institutional support, national recognition, or even much in the way of professional affirmation or encouragement beyond a very small circle of family and friends. In fifty years of writing, he produced a remarkable quantity, breadth and variety of literary work, including books of literary and philosophical essays, travel, autobiography, poetry, fiction, humour, fantasy, dramatic criticism, children’s literature, sporting memoirs and political commentary: thirty separate volumes, none of them sufficiently popular, even at the time of publication, to earn the writer a living or even give him a profile in Australia. His writings often have a startling freshness and independence, but very singularity that makes him interesting also makes him unusually resistant to categorization in terms of group affiliations and clearly defined literary and intellectual traditions.